Maximização do uso da uréia em lavoura de Coffea canephora - Rodrigues, José de Oliveira (2013)
The objective was to determine nitrogen losses by ammonia volatilization from ureas with increased efficiencies as well as the development and productivity of coffee Conilon handled with such ureas. The experiment was installed in October 2010 in the city of Nova Venezia - ES on a coffee plantation Conilon cultivar Victoria INCAPER 8142. We evaluated five sources of nitrogen fertilizers: T1 = urea pearly common (45% N), T2 = urea (45% N) + NBPT - (Super N®), T3 = urea (44.6% N) + 0.15 % of Cu2+ and 0.4% B - (More Nitro®); T4 = urea (37% N) + sulfur (17%) - (Nitro Gold®) and T5 = ammonium nitrate (34% N). The treatments T2, T3 and T4 are considered to "increased efficiency" and the T1 and T5 were used as control negative and positive respectively. The ammonia collectors were installed in each plot immediately after fertilizer application in three different seasons, and in October, December 2011 and March 2012. The sponges collecting ammonia (NH3) were exchanged at 5, 10 and 15 days. Were evaluated characteristics associated with the chlorophyll fluorescence. These evaluations were performed prior to fertilization in October and in January and March 20 days after fertilization. The branch growth was evaluated monthly for measuring the length of the branches by dialing three groups of branches growing randomly selected. Were scored four primary branches per plot. The first group of branches was evaluated and scored from 5 August 2011 and the second group from December 9, 2011 and the third group from April 12, 2012. The ammonium nitrate was the nitrogen source that had lower NH3-N loss through volatilization among the other nitrogen sources. The urea and urea + sulfur pearly were common sources of nitrogen that showed greater loss of nitrogen through volatilization in the second evaluation. Thus, it is assumed that precipitation was not sufficient to dissolve and incorporate the fertilizer, the soil remains moist, thereby increasing the activity of the enzyme urease on fertilizers. In general, urea and urea + NBPT + Cu2+ and B had the lowest volatilization losses from fertilizers with "increased efficiency". The different nitrogen sources did not cause significant differences in crop yields of 2011 and 2012. Values (Fv / Fm) did not differ in any of the times examined, suggesting that the nitrogen sources did not alter the efficiency of photosystem II. Relative values of Chlorophyll Index (CRI) alternated their significance with respect to treatments throughout the evaluation dates. The nitrogen sources did not significantly influence the growth of three groups of branches in all assessments.